2020
DOI: 10.21307/jepil-2020-001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of forced normalization and alternative psychosis with special consideration of the new anticonvulsants

Abstract: Background. In the case of an alternative psychosis (AP) or forced normalization (FN), the patient alternates between periods of clinically manifest seizures and normal behavior, and other periods of seizure freedom or significant seizure reduction accompanied by psychosis or behavioral disturbances. In clinical practice and in the literature, the terms AP and FN are mostly used synonymously despite small differences. FN of the EEG is not only common to interictal mental disturbances but may also occur in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…We also find a 60 % of patients with focal epilepsies and 20 % with focal/generalized epilepsies. This is the most frequent type of epilepsy according to the data from previous studies [10,11]. We found focal seizures (with or without impaired awareness) were the most frequent (80 % of patients).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We also find a 60 % of patients with focal epilepsies and 20 % with focal/generalized epilepsies. This is the most frequent type of epilepsy according to the data from previous studies [10,11]. We found focal seizures (with or without impaired awareness) were the most frequent (80 % of patients).…”
Section: Discussionsupporting
confidence: 55%
“…The fact that we did not find any case of forced normalization related to levetiracetam in our series is striking, despite it is the most frequently related antiepileptic drug, probably due to the fact that it is one of the most frequently prescribed antiepileptic drugs, according to Fröscher [10] and Calle-López [11]. Nevertheless, in these reviews forced normalization does not seem to be drug dependent.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…This author believes that this was FN caused by VGB. To date, there have been more than 13 patients with FN caused by VGB[ 1 ].…”
Section: Clinical Features Of Fnmentioning
confidence: 99%
“…FN is unique to the pharmacotherapy of epilepsy and often leads to the failure of epilepsy treatment. Although FN is still an entity with uncertain pathophysiology, it has received extensive clinical attention in recent years, and significant progress has been made regarding its pathogenesis and treatment strategies[ 1 - 5 ]. Recently, Calle-López et al [ 5 ] conducted a study on 193 FN episodes and found that the causes included antiseizure medications (ASMs), epilepsy surgery and vagus nerve stimulation (VNS), with ASMs being the most common cause.…”
Section: Introductionmentioning
confidence: 99%